Ответы и объяснения

2013-06-05T00:09:20+04:00

x+y+2xy=7 => 2x+2y+4xy=14 => 4xy + 2(x+y) = 14

Вычитаем второе уравнение:

4xy+2(x+y) - xy - 2(x+y) = 14 - 8

3xy = 6

xy = 2

Подставляем xy во второе уравнение: 

2+2(x+y)=8 => x+y=(8-2)/2=3

Итого:

\begin{cases} x\cdot y=2\\x+y=3\end{cases}

x=3-y

xy=(3-y)*y=2

y^2-3y+2=0

y_{1,2}=\frac{-b\frac{+}{}\sqrt{b^2-4ac}}{2a}=\frac{3\frac{+}{}\sqrt{9-4\cdot2}}{2}=\frac{3\frac{+}{}1}{2}

y_{1}=1

y_{2}=2

x_{1,2}=3-y_{1,2}

x_{1}=3-1=2

x_{2}=3-2=1

 

Ответ: 1) x=1, y=2; 2) x=2, y=1